Identifying infection sources in a network - Luo, Wuqiong (2015)
Modern networks like social, communication and transportation networks have grown drastically in complexity. Such networks are susceptible to rapidly spreading “infection”, which can have different meanings under different contexts, including a contagious disease, a computer virus or a rumor. Timely identification of the infection sources (the index cases of a contagious disease, the original servers that injected a computer virus into the Internet, or the rumor origins that started a rumor in a social network) is critical for limiting the damage caused by the infection. The infection sources identification problem has thus attracted considerable interest from the research community over the past few years.